Practicality of Using Alternative Energy Project Media in High School Physics Learning - Nurhativa Yusana; Y Yennita; Z Zulirfan (Science Education Department of Mathematics and Natural Sciences Education Faculty of Teacher Training and Education, Universitas Riau in collaboration with the Association of Indonesian Science Educators (PPII), 2023)
This development research aims to test physics learning media on alternative energy materials that have been designed and tested. The type of research used is Research and Development adapted from the theory of Borg and Gall. The learning media developed consists of experimental projects and project use books. The alternative energy media that has been developed consists of 3 projects, namely simple garden lights, simple watermills, and simple windmills. Data collection was carried out through practicality assessment sheets assessed by teachers and students. Aspects of the experimental project assessed include aspects of ease of use of tools and materials, ease of understanding the material, ease of packaging tools, usefulness, safety, and attractiveness. Meanwhile, the assessment aspect for the project use book includes the feasibility aspect of presentation, content accuracy, language feasibility, and display feasibility. The results of the practicality of the experimental project by teachers and students obtained an average score of >3 while the average results of the practicality of the book use of the project by teachers and students obtained an average score of >3. Thus, it can be concluded that alternative energy learning media is declared practical as a class X high school physics learning media.